Murine leukemias with retroviral insertions at Lmo2 are predictive of the leukemias induced in SCID-X1 patients following retroviral gene therapy. - Utpal P Davé; Keiko Akagi; Rati Tripathi; Susan M Cleveland; Mary A Thompson; Ming Yi; Robert Stephens; James R Downing; Nancy A Jenkins; Neal G Copeland (PLoS Genetics)
Five X-linked severe combined immunodeficiency patients (SCID-X1) successfully treated with autologous bone marrow stem cells infected ex vivo with an IL2RG-containing retrovirus subsequently developed T-cell leukemia and four contained insertional mutations at LMO2. Genetic evidence also suggests a role for IL2RG in tumor formation, although this remains controversial. Here, we show that the genes and signaling pathways deregulated in murine leukemias with retroviral insertions at Lmo2 are similar to those deregulated in human leukemias with high LMO2 expression and are highly predictive of the leukemias induced in SCID-X1 patients. We also provide additional evidence supporting the notion that IL2RG and LMO2 cooperate in leukemia induction but are not sufficient and require additional cooperating mutations. The highly concordant nature of the genetic events giving rise to mouse and human leukemias with mutations at Lmo2 are an encouraging sign to those wanting to use mice to model human cancer and may help in designing safer methods for retroviral gene therapy.